Thinking Processes in Skizoprenia Patients at The Efata Recovery House at Getasan - Luke Setyo Anggoro (Universitas Katolik Soegijapranata, 2018)
This study aims to determine the picture of thinking processes in schizophrenic patients. The subjects consisted of three people with schizophrenia who went into the residual phase. The approach used is qualitative method and use case study research design. In this study, the patterns of thinking contained in the subject include analogical thinking, concrete and scientific, but there are subjects who still think autistic. In addition, there are subjects who are better able to think creatively and logically, but the process of creative thinking is not shared by other subjects. Research subjects have difficulty in solving the problems they are experiencing, especially oneself and must need others in overcoming the problem, one of the subjects was afraid if he could not find a solution in his problem. All subjects are also still experiencing disruption of thought processes, such as: incoherence, preoccupation, flight of ideas and others. The interruption of thought processes can affect the subject in using his thinking pattern. Also in terms of self-acceptance, there is only one subject that still has not accepted its current state. Therefore, the thought process is very necessary for residual schizophrenia to be more productive, so that in the recovery period they can produce works and beneficial to others